2015
DOI: 10.1590/1982-0194201500012
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco de infecção da ferida operatória em neurocirurgia

Abstract: Objective: To analyze risk factors for surgery site infection in neurosurgery. Methods: A prospective cross-sectional study conducted in a tertiary hospital analyzing 85 elective and clean neurosurgeries with an outcome of infection within 30 days after surgery. Results: Surgical site infection occurred in 9.4% (n=8) of cases. Bivariate analysis revealed that the following risk factors were associated with the presence of infection: total length of hospital stay, Body Mass Index, surgical size and blood transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
(24 reference statements)
0
5
0
12
Order By: Relevance
“…(19) To this end, measures of control and prevention are fundamental and related to the postoperative treatment. Health care programs are necessary to address the characteristic aspects of individuals affected by this underlying disease not only during hospitalization, since many postoperative complications result from decompensation associated with this comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…(19) To this end, measures of control and prevention are fundamental and related to the postoperative treatment. Health care programs are necessary to address the characteristic aspects of individuals affected by this underlying disease not only during hospitalization, since many postoperative complications result from decompensation associated with this comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…(1) This direction was given to the instrument based on the evidence of care practice associated with literature findings on assessment of surgical care results, which showed that SSI is an avoidable complication of surgery. (1,(8)(9)(10)25) The prevalence of SSI is higher among healthcare-associated infections. (25) After instrument design and before effective care, scientific validation is required.…”
Section: Discussionmentioning
confidence: 99%
“…(7) SSI is the most frequent complication in patient who have undergone surgery. (8) It contributes to about 31% of all healthcare-associated infections (9) and to about 37% of infections in surgical patients acquired in the hospital. (1,10) In Brazil, SSI is ranked third among all healthcare services-associated infection.…”
Section: Introductionmentioning
confidence: 99%
“…Procedimentos invasivos são associados a ocorrência de infecções por multirresistentes. [6][7][8] Quando se trata de Infecção Hospitalar (IH), o conceito compreende não só as originárias de uma internação, mas, também infecções oriundas antes da admissão do paciente desde que relacionadas a procedimentos hospitalares, utilizando um termo mais abrangente, fala--se em infecção relacionada a serviços de saúde. Seus impactos incluem o aumento do tempo de permanência do paciente nos serviços de saúde e consequentemente mais gastos.…”
Section: -3unclassified